Nitrogen and phosphorus availabilities interact to modulate leaf trait scaling relationships across six plant functional types in a controlled-environment study - Crous, Kristine Y (The New phytologist, 2017)
© 2017 The Authors. New Phytologist © 2017 New Phytologist Trust.